An Analysis of Polysemy in the Song Lyrics ‘Shape of You’ by Ed Sheeran: A Lexical Semantics Study - Octania Romaito Rajagukguk; Bernieke Anggita Ristia Damanik (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates polysemy in Ed Sheeran’s “Shape of You” using a non-empirical qualitative design grounded in lexical semantics. The research aims to identify polysemous lexical items, examine their contextual meanings, and analyze their semantic functions in shaping lyrical interpretation. Data were obtained from the official song lyrics and analyzed through descriptive textual analysis involving lexical identification, contextual classification, and semantic interpretation. The findings reveal that numerous lexical items such as “shape,” “heart,” “fall,” and “touch” exhibit systematic meaning extensions between literal and metaphorical domains. Context plays a crucial role in determining meaning selection, allowing lexical ambiguity to function as a controlled interpretive mechanism. The study further shows that polysemy contributes to aesthetic structuring, emotional intensification, and communicative efficiency within the lyrics. These functions demonstrate that lexical meaning in song discourse is dynamically constructed rather than fixed. Overall, polysemy operates as a central semantic strategy that enhances both interpretive depth and artistic expression in contemporary popular music.